2005
DOI: 10.1007/11608288_71
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Feature and Score Normalization for Speaker Verification

Abstract: In speaker verification, it is necessary to reduce the influence of different environmental conditions. In this paper, two stages of normalization techniques, feature normalization and score normalization, are examined for decreasing the mismatch between training and testing acoustic conditions. At the first stage, cepstral mean and variance normalization (CMVN) is modified to normalize the cepstral coefficients with the similar segmental parameter statistics. Next, due to score variability between verificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…CMVN reduces the effect of additive environmental noises from the feature vectors and it was previously shown that it improves the recognition rate in speaker recognition [33].…”
Section: Feature Normalizationmentioning
confidence: 98%
See 2 more Smart Citations
“…CMVN reduces the effect of additive environmental noises from the feature vectors and it was previously shown that it improves the recognition rate in speaker recognition [33].…”
Section: Feature Normalizationmentioning
confidence: 98%
“…CVN has more impact on reducing the effect of additive environmental noise from feature vectors than CMN operation. However, in many speech and speaker recognition studies, CMN and CVN are combined which yields to have feature vectors with zero mean and unit variance which is known as cepstral mean and variance normalization (CMVN) [4,33]:…”
Section: Feature Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Minimum Value of Detection Cost Function (minDCF) [14] Application scenarios have different requirements for false-alarm and miss rates. Thus, the setting of the threshold needs to be adjusted accordingly.…”
Section: Evaluation Measuresmentioning
confidence: 99%
“…The effect of the model normalisation can be observed in Figure 3 (f). This normalisation is called ZT-norm and in [11] a reduction of 20% EER is reported when compared with standard Z-Norm.…”
Section: Model Normalisationmentioning
confidence: 99%